Virulence Characterization of Faecal Escherichia coli Isolates from Wild Animals - Kumar, Kamlesh; Sannat, Chandrahas; Hirpurkar, Sadanand Devidas; Rawat, Nidhi; Singh, Jasmeet; Sahu, Savita; Ratnayke, Rajat; Dilliwar, Vishvajeet (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was undertaken to characterize virulence factors associated with fecal Escherichia coli (E.coli) isolates (n=22) from wild animals. Isolates were phenotypically characterized for haemolytic, haemagglutination and gelatinase activity whereas presence of adhesion genes viz. fimH and papG1 was detected genotypically by PCR. Further, whole blood survival assay of E. coli isolates (n=6) was performed using human and goat blood. Isolates exhibited heamolytic (45.45%) as well as gelatinase activity (27.27%) and led mannose sensitive agglutination of human (45.45%), dog (40.90%) and chicken (27.27%) RBC.  fimH gene was detected in 27.27% of the isolates whereas none of the isolates was found positive for PapG1 gene. Isolates survived, got adapted and then grew successfully in human as well as goat blood. It can be concluded from present study that wild animals are potent reservoir of virulent E. coli that could adversely affects in-contact human and livestock population.
Keywords: Wild animals; Feacal E.coli; Haemagglutination; Gelatinase; fimH